Pelatihan Pembuatan Dan Penggunaan Google Classroom Dan Zoom Pada Guru SD Swasta Gemilang Berastagi - Yuyun Dwi Lestari; Arief Budiman; Yessi Fitri Annisa; Muhammad Eka; Ilham Faisal (Jurnal TUNAS, 2021)
The rapid development of technology today is very much felt by all groups, both from the government, health, education, and so on. Especially with the impact of the current pandemic, we must be able to use technology to be able to complete work according to our respective fields of work. The existence of rules to comply with health protocols in the field of education has resulted in the implementation of teaching being done online. Online teaching has an impact on teachers and students in schools in implementing learning. The utilization of technology can be used as a solution in the implementation of the teaching to be effective. However, there are still many teachers who have not been able to take advantage of it, due to the lack of information about it. For that, we need applications that can be used to manage and facilitate teaching to be more effective, such as the Google Classroom and Zoom applications. Google Classroom and Zoom are very easy to access as learning media because these applications are not paid or free and can be accessed via a laptop or smartphone via Google Playstore. Community service activities took place at Gemilang Berastagi Private Elementary School, Karo Regency for many teachers who still did not know about the use of Google Classroom and Zoom applications. The material provided is in the form of creating an account for the Google Classroom and Zoom applications, then explaining the features, as well as how to use each of the Google Classroom and Zoom applications. Thus, teachers at Gemilang Private Elementary School can understand how to use and utilize the features found in Google Classroom and Zoom as online learning and teaching media during the current pandemic.